Adventures in Pedagogy: The Trials and Tribulations of Teaching Common Law in China - Sam Blay; Angus Young; Grace Li (Legal Education Review)
The Queensland University of Technology (QUT) University Academic Board approved a new QUT Assessment Policy in September 2003, which requires a criterion-referenced approach as opposed to a norm-referenced approach to assessment. In 2004, in accordance with the QUT Implementation Plan, the QUT School of Law raised an awareness of criterion-referenced assessment and implemented criterion-referenced assessment in first year core undergraduate law units. The Implementation Plan anticipates that all law units across all year levels will implement criterion-referenced assessment between 2005 and 2007. This teaching note will distinguish norm-referenced assessment from criterion-referenced assessment and justify why QUT is implementing criterion-referenced assessment. It will focus on how the authors of this article designed, implemented and evaluated criterion-referenced assessment in a first year core undergraduate law unit, LWB143 Legal Research and Writing, in 2004. In 2004, the unit had a cohort of approximately 600 students and 12 members in the teaching team. Ten members of the teaching team were involved in marking the items of assessment and eight of them were casual academics. In light of the experience in 2004, the authors provide some insight into the way forward.